Perspectives on an enhanced 'Improving Access to Psychological Therapies' (IAPT) service addressing the wider determinants of mental health: a qualitative study - Esther Louise Curtin; Katrina d'Apice; Alice Porter; Emily Widnall; Matthew Franklin; Frank de Vocht; Judi Kidger (BMC, 2023)
Abstract Background A new Health and Wellbeing pathway was introduced into the Improving Access to Psychological Therapies (IAPT) service in one geographical area of the UK in 2021 to address the wider determinants of mental health problems. It comprised assisted signposting to wider services and physical health promotion. This qualitative study aimed to understand stakeholders' experiences of implementing and receiving this new support and the barriers and facilitators to its delivery. Methods Forty-seven interviews were conducted, with service developers (n = 6), service deliverers (n = 12), service users (n = 22) and community and clinical partners (n = 7), as part of a larger mixed-methods evaluation. Interviews were recorded, transcribed, and analysed using reflexive thematic analysis. Results Three themes spanned all participant groups and represented key aspects of the service: (1) identifying suitability, (2) a holistic service, and (3) moving forward. The sub-themes represent the barriers and facilitators to processes working in practice, lending insight into potential service improvements. These included strengthening the quality of communication during referral and assessment, tailoring the support and delivery mode, and increasing transparency around continued care to drive sustained benefits. Limitations Service users may have been selected due to their positive experiences of IAPT and were not demographically representative of the population, although participants' experiences of the service did suggest variation in our sample. Conclusions The Health and Wellbeing pathway was perceived as having a positive impact on mental health and could reduce the burden on therapeutic services. However, service- and individual-level barriers need to be addressed to enhance statutory and community support links, manage service users' expectations, and improve accessibility for certain groups.